Production and consumption-based accounts of Ireland's emissions - Kelly C. De Bruin; Çağaçan Değer; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2024)
This paper aims to calculate emissions in Ireland by applying a production-based Accounting (PBA) approach and a consumption-based Accounting (CBA) approach. PBA considers emissions in Ireland to be all emissions emitted in the geographic region of Ireland, whereas CBA includes all emissions resulting from the consumption of residents of Ireland. CBA accounts for emissions embedded in trade, where production-related emissions embedded in goods imported into Ireland are assigned to Ireland, whereas the production emissions of goods produced in Ireland which are exported are discounted from Ireland's emissions. Applying GTAP 11 data, our estimates show that CBA emissions for Ireland are between 8% and 16% larger than PBA emissions, depending on assumptions regarding the allocation of electricity and cattle-related emissions. The emissions embedded in international trade are embedded in the flows with Ireland's major trade partners: the United Kingdom, the United States of America, Germany, China and Russia. Imported emissions are concentrated in the fuel, chemical products and services sectors.
Keywords: Q51; Q56; Q57; 330; consumption-based accounting; production-based accounting; trade embedded emissions